4,083 UMP students graduate in 16th MKK - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 6 August 2022 - The Universiti Malaysia Pahang (UMP) 16th Convocation Ceremony today saw a total of 4,083 graduands for 2021, comprising doctoral and master’s graduands (280), bachelor’s graduands (2,235) and diploma graduands (506) as well as UMP Advanced graduands (1,062) receiving their degrees and diplomas from 6 to 9 August at the Sports Complex, UMP Gambang Campus.